(untitled) (Cadernos de Sociomuseologia, 2024)
In Brazil, there is a growing focus on the theme of "cultural accessibility for people with disabilities" and an expansion of initiatives in this direction, however, it is still necessary to strengthen public policies that promote cultural citizenship. This article aims to reflect on the context of cultural accessibility for people with disabilities. It discusses initiatives aimed at enhancing the cultural rights agenda for this population, as well as strategies to engage various cultural sector agents in improving the cultural capital of people with disabilities. The historical processes of exclusion, invisibility, and prejudice remain barriers to be addressed. Furthermore, the socio-cultural condition of people with disabilities in Brazil and globally has emerged as a significant issue, given the goal of promoting sustainable development. The article concludes that community-based cultural initiatives are essential for promoting the cultural citizenship of people with disabilities and those in situations of social vulnerability. In this regard, the perspective of sociomuseology can be an important ally in advancing the cultural citizenship of this population. Keywords: Cultural accessibility. People with Disabilities. Community-based culture. Sociomuseology. Social Vulnerability. Cultural Citizenship.